Tradisi Hasae Batar Manaik dalam Suku Tafatik Leko A di Desa Wehali Kabupaten Malaka - Angela Hoar Klau; Antonius Bere; Clotilde Seran; Yohanis Kristianus Tampani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study examines the implementation of the Batar Manaik tradition, a corn-honoring ritual performed annually by indigenous communities, particularly during the corn harvest season. This tradition is not only a form of gratitude for the harvest but also embodies cultural values that strengthen social bonds within the community. The ritual process involves various parties, including farmers, clan leaders (fukun), and community figures, each with important roles and responsibilities. The execution of the tradition begins with a series of stages involving the use of cultural symbols, such as tied corn, chicken blood, and the traditional house (ai lotuk laran) as the center of the ritual. Every tool and material used in the ritual, such as torches and mats, holds deep symbolic meaning. Through this tradition, the community not only celebrates the harvest but also reinforces their cultural identity and spiritual connection with their ancestors and the surrounding environment. This research aims to uncover the significance of each element involved in the BatarManaik ritual and how community participation affects the preservation of this tradition in the modern era.